CENTRAL ASIA – DEVELOPMENTS, CHALLENGES, STRATEGIES, PERSPECTIVES - Paraschiva Bădescu (Romanian Journal of Historical Studies, 2021)
Central Asia is the place where populations, conquerors, cultures and ideas have swept across the regions steppes, deserts and mountains for thousands of years, and has been the focus of ancient EastWest trade routes collectively called „The Silk Road”; it was the board on which the „Great Game” between big actors was played. The region represents the most concentrated mass of wealth in the world; these riches are becoming the stake in a new economic Great Game and new Silk Road. The study presents the situation and evolution of the new independent States, different structures and mechanisms of their cooperation, used for coordinating their policies and creating a balance to western oriented organizations, involvement and assistance provided by international fora to build their capacity in different fields. The area remains a ground of increased interests and competition, mainly between Russia, US and China, indicating perspectives for building a new Silk Road.